Vacuum drying of garlic powder - Tagayuna, Florentina M.
The study was undertaken to develop a standard procedure for vacuum drying of garlic powder. Variables studied were the drying temperatures(120°F, 140°F, 160°F, 180°F) and peeling treatment using different concentrations of HCl solutions with different time of exposure (2 hrs., 3 rs., 5 hrs., 8 hrs.). A chloride test was done on samples exposed to HCl fumes. Those that gave negative results were further analyzed by using the optimum drying temperature obtained and powdering them in an air-conditioned room to avoid reabsorption of moisture. A simple linear correlation was also done on two variables such as the percentage of oil retained after dehydration and the total panel scores for flavor obtained in the sensory evaluation. Results showed that there was a strong linear relationship between the variables. Objective and subjective tests indicated that the product dried at 160°F and exposed for 2 hours in 37% HCl solution gave the best sample. It was yellowish-white in color with characteristic garlic odor and flavor.